Smoking and Idiopathic Pulmonary Fibrosis - Chad K. Oh; Lynne A. Murray; Nestor A. Molfino (Pulmonary Medicine)
Idiopathic pulmonary fibrosis (IPF) is a disease of unknown etiology with considerable morbidity and mortality. Cigarette smoking is one of the most recognized risk factors for development of IPF. Furthermore, recent work suggests that smoking may have a detrimental effect on survival of patients with IPF. The mechanism by which smoking may contribute to the pathogenesis of IPF is largely unknown. However, accumulating evidence suggests that increased oxidative stress might promote disease progression in IPF patients who are current and former smokers. In this review, potential mechanisms by which cigarette smoking affects IPF, the effects of cigarette smoking on accelerated loss of lung function in patients with IPF, key genetic studies evaluating the potential candidate genes and gene-environment (smoking) interaction, diagnosis, and treatment with emphasis on recently closed and ongoing clinical trials are presented.